Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1155/2016/6817502
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of DNA Topoisomerase Type IIα(TOP2A) by Mitoxantrone and Its Halogenated Derivatives: A Combined Density Functional and Molecular Docking Study

Abstract: In this study, mitoxantrone and its halogenated derivatives have been designed by density functional theory (DFT) to explore their structural and thermodynamical properties. The performance of these drugs was also evaluated to inhibit DNA topoisomerase type IIα (TOP2A) by molecular docking calculation. Noncovalent interactions play significant role in improving the performance of halogenated drugs. The combined quantum and molecular mechanics calculations revealed that CF3 containing drug shows better preferen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 63 publications
0
13
0
Order By: Relevance
“…TOP2A is a widely used target of existing anti-cancer drugs and it's expression is often used as a cancer cell marker because of it's role in cell proliferation [ 61 ]. Indeed, it is the only protein identified in our dataset that is targeted by currently FDA approved drugs for PCa.…”
Section: Discussionmentioning
confidence: 99%
“…TOP2A is a widely used target of existing anti-cancer drugs and it's expression is often used as a cancer cell marker because of it's role in cell proliferation [ 61 ]. Indeed, it is the only protein identified in our dataset that is targeted by currently FDA approved drugs for PCa.…”
Section: Discussionmentioning
confidence: 99%
“…Mitoxantrone (Novantrone) is an anticancer drug that inhibits the DNA topoisomerase II activity which results in preventing the DNA synthesis process, and inhibiting cellular proliferation. 109 This drug was approved for the treatment of RRMS, SPMS, and PRMS, where it acts as an immunosuppressant inhibiting immune cells proliferation, their antigen presentation and inflammatory cytokines secretion. 110 A study by Scott et al 111 showed that intravenous treatment of MS patients with mitoxantrone reduced the relapse rate and delayed the progression of the disease.…”
Section: Role Of Mitoxantrone In Modulating Chemokines and Chemokine mentioning
confidence: 99%
“…Mitoxantrone anticancer drug is known to do its anticancer activity via DNA intercalation, inhibition of transferase human CDK2 and inhibition of topoisomerase II [33][34][35][36].…”
Section: Molecular Docking and Binding Energy Calculationsmentioning
confidence: 99%